A time-dependent atomistic reconstruction of severe irradiation damage and associated property changes in nuclear graphite. (August 2017) - Farbos, Baptiste; Freeman, Helen; Hardcastle, Trevor; Da Costa, Jean-Pierre; Brydson, Rik; Scott, Andrew J.; Weisbecker, Patrick; Germain, Christian; Vignoles, Gérard L.; Leyssale, Jean-Marc
Abstract: Detailed knowledge regarding the nature of and mechanisms causing neutron irradiation damage in graphite remains a scientific and technological challenge, particularly at high irradiation doses. Using electrons as a surrogate for neutron irradiation, we develop a time-dependent atomistic reconstruction strategy fed by a time series of high-resolution transmission electron microscopy (HRTEM) images, to monitor damage propagation in a graphite grain up to a dose of about one displacement per atom ( i.e. well beyond the conventional irradiation simulations based on molecular dynamics). The reduction in crystalline order and the development of interlayer bonding observed in the models with increasing irradiation time induce significant modifications of the elastic constants and thermal conductivity. Homogenizing these properties to the case of isotropic polycrystalline graphite we are able to reproduce the increase in Young's modulus and decrease in thermal conductivity observed experimentally for reactor graphites with increasing dose. Further validation of the models is provided via a comparison of simulated and experimental data from irradiated material such as: HRTEM images, carbon K-edge electron energy loss spectra, dose rate and stored energies. Graphical abstract: